The World English Bible (WEB): Daniel - Anonymous (Salt Lake City, UT : Project Gutenberg, 2005)
"The World English Bible (WEB): Daniel" by Anonymous is a religious text from the early centuries AD, belonging to the genre of biblical scripture. It presents a narrative that focuses on the life and prophecies of the prophet Daniel, emphasizing themes of faith, divine intervention, and the struggles of the Jewish people during their exile in Babylon. The book is rich in historical context and allegorical subtext, reflecting the challenges faced by both individual believers and the Jewish community as a whole. In this text, Daniel, a young Hebrew of noble lineage, is taken captive by Nebuchadnezzar, king of Babylon. The story unfolds through a series of vivid dreams and divine revelations, offering interpretations that foretell the rise and fall of empires. Key figures include Daniel and his friends, who refuse to worship the Babylonian gods, leading to dramatic confrontations, such as their survival in a fiery furnace. The book also features prophetic visions that outline the future of world powers and the ultimate triumph of God's eternal kingdom. Daniel's unwavering faith and remarkable wisdom serve as central themes, inspiring readers with messages of hope and perseverance amidst adversity. (This is an automatically generated summary.)
Release date is 2005-06-01
From www.ebible.org with slight reformatting by Martin Ward
Keywords: Bible. Daniel